Marthamea bayae, a new species of stonefly from Algeria (Plecoptera: Perlidae) - Lamine, Smail; Lounaci, Abdelkader; Reding, Jean-Paul G.; Vinçon, Gilles (Zootaxa, 2019)
A new species of the perlid genus Marthamea Klapálek, M. bayae sp. n. from Algeria is described and illustrated based on the morphology of adults and larvae. This is the first known record for the genus from North Africa.